Kinetics of interaction between substrates/substrate analogs and benzoate 1,2-dioxygenase from benzoate-degrading Rhodococcus opacus 1CP - Solyanikova, Inna P; Borzova, Oksana V; Emelyanova, Elena V (Folia microbiologica, 2017)
Benzoate 1,2-dioxygenase (BDO) of Rhodococcus opacus 1CP, which carried out the initial attack on benzoate, was earlier shown to be the enzyme with a narrow substrate specificity. A kinetics of interaction between benzoate 1,2-dioxygenase and substituted benzoates was assessed taking into account the enlarged list of the type of inhibition and using whole cells grown on benzoate. The type of inhibition was determined and the constants of a reaction of BDO with benzoate in the presence of 2-chlorobenzoate (2CBA), 3,5-dichlorobenzoate (3,5DCBA), and 3-methylbenzoate (3MBA) were calculated. For 2CBA and 3MBA, the types of inhibition were classified as biparametrically disсoordinated inhibition and transient inhibition (from activation towards inhibition), respectively. The process of not widely recognized pseudoinhibition of a BDO reaction with benzoate by 3,5DCBA was assessed by the vector method for the representation of enzymatic reactions. Ki value was determined for 2CBA, 3MBA, and 3,5DCBA as 337.5, 870.3, and 14.7 μM, respectively.
Keywords: benzoáty; bakteriální proteiny; Benzoates; Rhodococcus; substrátová specifita; oxygenasy; kinetika; Biodegradation, Environmental; Oxygenases; Bacterial Proteins; Kinetics; Substrate Specificity; biodegradace